2017
DOI: 10.1038/s41598-017-10283-4
|View full text |Cite
|
Sign up to set email alerts
|

(S)-Oxiracetam is the Active Ingredient in Oxiracetam that Alleviates the Cognitive Impairment Induced by Chronic Cerebral Hypoperfusion in Rats

Abstract: Chronic cerebral hypoperfusion is a pathological state that is associated with the cognitive impairments in vascular dementia. Oxiracetam is a nootropic drug that is commonly used to treat cognitive deficits of cerebrovascular origins. However, oxiracetam is currently used as a racemic mixture whose effective ingredient has not been identified to date. In this study, we first identified that (S)-oxiracetam, but not (R)-oxiracetam, was the effective ingredient that alleviated the impairments of spatial learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 67 publications
(78 reference statements)
0
18
0
1
Order By: Relevance
“…Rats were anesthetized with an intraperitoneal injection of pentobarbital sodium (60 mg/kg) [31]. Brain tissue was collected and frozen at −20 • C for 30 min, and 2 mm brain slices [32] of the coronal plane were prepared and placed in 2% TTC/phosphate-buffered saline (PBS) solution and incubated at 37 • C for 15 min in the dark.…”
Section: Infarct Volume and Edema Damage Assessmentmentioning
confidence: 99%
“…Rats were anesthetized with an intraperitoneal injection of pentobarbital sodium (60 mg/kg) [31]. Brain tissue was collected and frozen at −20 • C for 30 min, and 2 mm brain slices [32] of the coronal plane were prepared and placed in 2% TTC/phosphate-buffered saline (PBS) solution and incubated at 37 • C for 15 min in the dark.…”
Section: Infarct Volume and Edema Damage Assessmentmentioning
confidence: 99%
“…Intriguingly, the contrary phenomenon was observed upon administration of the ROCK inhibitor Y-27632. Furthermore, the free-radical scavenger edaravone and neuroprotective agent oxiracetam decreased ion OP and PN-OP distinctly, suggesting that elimination of intracellular toxic substances such as reactive oxygen species induced by glutamate could contribute to a reduction in cytoplasmic OP [10], [68], [69]. We speculated that cytotoxic astrocyte swelling might be a self-protection measure for diluting the toxic substances generated, similar to an inflammatory reaction.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, ORC demonstrated the protective capacity to suppress the secondary damage derived from Aβ-induced activation of microglia, which indicates that ORC may also have a positive effect on indirect toxicity in complex in vivo systems. In addition, many previous studies have also reported that ORC improves abnormal mitochondrial oxidative phosphorylation and subsequent ATP metabolism (19,47). ORC has also been shown to alleviate middle cerebral artery occlusion/reperfusion-induced BBB dysfunction, another pathology observed in patients with AD.…”
Section: Discussionmentioning
confidence: 97%
“…Oxiracetam (ORC) is a nootropic of the racetam family; it has been examined for its potential use in the treatment of cognitive impairment ( 15 ), cerebrovascular diseases ( 16 ), and multi-infarct dementia ( 17 ), because it can readily pass through the blood–brain barrier (BBB) and act selectively on the cortex and hippocampus ( 18 ). Recent reports have suggested that ORC improves memory in a rat model of vascular dementia and promotes recovery of cognitive function in a rat model of cerebral hypoperfusion ( 19 ). Furthermore, ORC remarkably reverses cognitive decline in older human subjects ( 20 ).…”
Section: Introductionmentioning
confidence: 99%